Hubungan Derajat Kelainan Radiologik dengan Derajat Nyeri pada Penderita Osteoartritis Sendi Lutut di Rumah Sakit Umum Daerah Kota Kendari - Iis Ainu Rahma; Mario Polo Widjaya; Muhammad Rustam; Agussalim Ali (Halu Oleo University, 2019)
Background: Osteoarthritic (OA) is a degenerative disease with slow progressive which has a characteristic pathological sign of joint deterioration as a result of biochemical, metabolic, physiological, and pathological changes. Pain is a complaint that is generally felt by people with osteoarthritis and has a different degree in each patient. Purpose: The purpose of this study determine the correlation between radiological abnormalities staging and pain level with osteoartritic of knee joint of Rumah Sakit Umum Daerah Kota Kendari. Method: This research is an observasional analytic study with cross-sectional approach. 37 sampels were acquired through total sampling. Data were analyzed using the Spearman correlation test (p value <0,05). Result: Result of the univariat analysis show that most patients have moderate radiological abnormality that were 12 (32.43%) and most of patient have severe pain level that were 19 (51.35%). Based on bivariat statistical test, a positive correlation was obtained between radiological abnormalities staging and pain level with osteoartritic of knee joint with p=0,000 and r=0,831. Conclusion: There was a significant correlation between radiological abnormalities staging and pain level with osteoartritic of knee joint of Rumah Sakit Umum Daerah Kota Kendari.Keywords: Osteoarthritic, Radiological abnormalities staging, Pain level